Structural and chemical characterization of the hardening phase in biodegradable Fe–Mn–Pd maraging steels. Issue 9 (12th May 2014) - Moszner, F.; Gerstl, S.S.A.; Uggowitzer, P.J.; Löffler, J.F.
Abstract